(untitled) - Grilli, Enzo R. (Baltimore, 1980)
In order to put in perspective some of the choices that natural rubber producing countries will have to make, this study assesses the magnitude and scope of the changes that have recently occurred in the rubber economy throughout the world and the likely consequences of these changes on the future of the world natural rubber industry.
Keywords: Rubber industry and trade,Công nghiệp cao su và thương mại